Controlled aggregation of gold nanoparticle networks induced by alkali metal ions - Tamang, Sudarsan; Hotha, Srinivas; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2007)
Gold nanoparticle networks were obtained by linking them with cysteine modified triethyleneglycols. The oligo-ether linker molecule initially having a linear structure probably adopts a crown ether type structure upon complexation with alkali metal ions that leads to a controlled aggregation of the network. The extent of aggregation depends on the degree of conformational change in the molecule upon complexation with the metal ion, which in turn is governed by the metal ion radius leading to a dependence of red shift of the surface plasmon resonance on the metal ion radius. Since this network is present in the organic solvent they also act as phase transferring agent for the alkali metal ions from aqueous to organic media.
Keywords: Aggregation; Alkali Metal Ions; Au Nanoparticles; Crown Ether; Surface Plasmon Resonance

Isolation, structure, and functional elucidation of a modified pentapeptide, cysteine protease inhibitor (CPI-2081) from streptomyces species 2081 that exhibit inhibitory effect on cancer cell migration - Singh, Jay Prakash; Tamang, Sudarsan; Rajamohanan, P. R.; Jima, N. C.; Chakraborty, Goutam; Kundu, Gopal C.; Gaikwad, Sushama M.; Khan, Mohammad Islam (Journal of Medicinal Chemistry, 2010)
Cysteine proteases play an important role in cell migration and tumor metastasis. Therefore, their inhibitors are of colossal interest, having potential to be developed as effective antimetastatic drugs for tumor chemotherapy. Traditionally, secondary metabolites from streptomyces show a wide range of diversity with respect to their biological activity and chemical nature. In this article, we have described the characterization of small molecule cysteine protease inhibitor, CPI-2081 (compound 1), a mixture of two novel pentapeptides, compound 1a (736.71 Da), and compound 1b (842.78 Da), isolated from Streptomyces species NCIM2081, following solvent extraction and repeated HPLC based on C18 chemistry, and completely characterized using a variety of both ID and 2D NMR spectroscopy. Further, it was found that nanomolar concentration of compound 1 is able to inhibit papain hydrolytic activity. Also, compound 1 significantly inhibits tumor cell migration at sub cytotoxic concentration, indicating its remarkable potential to be developed as antimetastatic drug, which will make chemotherapy more localized and specific, thereby minimizing the hazardous side effects on normal tissues.